The EU can manage without Russian liquified natural gas - Ben McWilliams; Giovanni Sgaravatti; Simone Tagliapietra; Georg Zachmann (Bruegel, 2023)
The European Union has committed to eliminate all Russian fossil-fuel imports by 2027. Progress has been made, with sanctions on oil and coal already introduced. The glaring exception is natural gas, on which the EU has so far refrained from imposing limitations, owing to greater dependence on Russia. Nevertheless, pipeline gas imports have fallen by four-fifths following Russia's weaponisation of gas supplies. However, Russia's exports of liquified natural gas (LNG) to the EU have increased since the invasion of Ukraine. The EU needs a coherent strategy for these LNG imports. Our analysis shows that the EU can manage without Russian LNG. Anticipated impacts are not comparable to those felt in 2022 as Russian pipeline gas dried up. The regional impact would be most significant for the Iberian Peninsula, which has the highest share of Russian LNG in total gas supply. Meanwhile, the global LNG market is tight, and we anticipate that Russia would find new buyers for cargos that no longer enter Europe. We discuss the options available to the EU. Wait-and-see implies delaying any action until 2027, while soft sanctions would discourage additional purchases but not break long-term contracts. We argue instead for an EU embargo on Russian LNG, to reduce exposure to an unreliable and adversarial entity, and to limit the extent to which EU consumers fund the Russian state. The embargo may be designed to allow purchases only if they are coordinated via the EU's Energy Platform, with limited volumes and below market prices. This could be accompanied by the implementation of a price cap on Russian LNG cargos that use EU or G7 trans-shipment, insurance or shipping services.
Keywords: 330